Respuesta :

Answer: x=-46

Step-by-step explanation:

Assuming the expression equals 0 (I'm not sure since you didn't explicitly state that, but I inferred for the sake of answering the question):

4(-8x+5)-(-33x-26)=0

-32x+20+33x+26=0

1x+46=0

x=-46

Hope that helps!

Answer:

x+46

Step-by-step explanation:

I used distribution for the first half of the equation, and got -32x+20. I used the negative on the second and mad it positive: 33x+26. I combine like terms, adding 33 to -32, got 1, then added 20 and 26. My answer was as listed above.

Hope this helped!